From Diagnosis to Development: Applying a Weighted 13A Framework to Assess Pigago Island's Tourism Competitiveness - Sembara Btr; Pasaribu; Trisna Putra (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
Island micro-destinations in emerging economies often have abundant natural resources but face governance challenges and lack effective diagnostic tools. This research introduces the initial empirical application of the weighted destination performance index (WDPI) based on the 13A framework, which includes Awareness, Attractiveness, Availability, Access, Appearance, Activities, Assurance, Appreciation, Action, Accountability, Accommodation, Amenities and Ancillary Services, and Altruism. The case study on Pigago Island, West Sumatra, Indonesia, uses a mixed-methods approach, structured observation, interviews with 25 participants, and systematic Instagram content analysis of 100 posts, rating each attribute on a 1-5 scale and weighting them via expert elicitation. The WDPI advances understanding of destination competitiveness by addressing the natural asset trap, in which high natural capital hinders investment in governance and scenic assets fail to translate into lasting visitor benefits. Pigago's WDPI score of 2.66 classifies it as an Emerging Destination. Key contributions include a replicable diagnostic tool, a phased investment plan with institutional roles, and an attribute-weighting protocol suitable for resource-limited settings. While designed for island micro-destinations, this framework is adaptable to various destination types, and initial validation encourages further comparisons.